PENINGKATKAN AKTIVITAS DAN HASIL BELAJAR BIOLOGI MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DISERTAI PERMAINAN BOWLING KAMPUS DI KELAS XI IPA.2 SMA NEGERI 1 TAMBUSAI KABUPATEN ROKAN HULU - SITI DUOLAM (JURNAL PENDIDIKAN ROKANIA, 2019)
This study aims to reveal the increase in Biology studentlearning activities and outcomes through the STAD typecooperative learning model accompanied by campusbowling games. This study is a Classroom ActionResearch (CAR) conducted in three cycles. Each cycleconsists of four steps: planning, action, observation,and reflection. The subject of this study was class XIIPA.2 Tambusai 1 Public High School with 25 students.To get this data, researchers used two instruments,namely observation sheets of student activity and resultsof student Biology tests. Student activities for each givenindicator were analyzed using percentage techniques.Improved learning outcomes can be seen from thenumber of students who complete according to theMinimum Completion Criteria (KKM). The results ofdata analysis in the first, second, and third cyclesshowed that there was an increase in student learningactivities in each indicator. The average percentage ofstudent activity increased from 71.11% in the first cycleto 80.58% in the second cycle and 86.69% in the thirdcycle. This contributes positively to student learningoutcomes. The number of students completing accordingto KKM increased from 64.00% in the first cycle to76.00% in the second cycle, and 88.00% in the thirdcycle. In general, it can be concluded that the application of the STAD type cooperative learningmodel with campus bowling games can improve studentlearning activities and outcomes.